Evaluating hazard conditions of plant colonization in Pasargadae World Heritage Site (Iran) as a tool of biodeterioration assessment. (May 2021) - Zohreh Hosseini,; Caneva, Giulia
Abstract: Plant colonization in the archaeological areas, despite its relevant role for monument conservation, has not dedicated noticeable concern. For the first time in Iran, we carried out a floristic evaluation in an archaeological area and its biodeterioration hazard, choosing Pasargadae WHS. Among the 142 detected species, found in the 9 study areas of the site, 48 ruderal common species resulted widely distributed, with a dominance of grasses (mainly Therophytes and Hemicryptophytes) belonging to the Asteraceae and Poaceae families. The analysis of plant colonization identified 10 possible Micro-Sites of growth (MS = place of growth on stone observed at small scale), half of which are described for the first time. Besides the life forms of plants, plant colonization in specific MS was selected as a parameter for hazard evaluation. Then, we coupled this information with five determinant parameters for plant growths, having each one three classes of value to obtain the final evaluation. The colonization in joints and fractures of stone blocks, as well as the surface covered by soil, represent the highest hazard conditions for biodeterioration. Green-gray sandy limestone, which was used as a platform for palaces, had the highest colonization. The collected data will contribute to the site management. Graphical abstract: Image 1 Highlights: The first floristic study on harmful flora in the archaeological sites of Iran. An evaluation of characteristics of harmful flora in arid bioclimate conditions. A methodological contribution to the indirect risk assessment of higher plant colonization. A proposal of microsite classification as a parameter for analyzing biodeterioration phenomena. An assessment of hazard risk from plant colonization of Pasargadae.